(untitled) (Latakia University Journal -Biological Sciences Series, 2020)
Crustaceans Amphipoda have important role in chains and food nets in the marine environment, they are source of food for large benthic fish and invertebrates, also they are one of important bio indicator of pollution and they contribute in cleaning the environment. This research aims to identify new species of Crustaceans Amphipoda spread among algae and hydrides, also to contribute in the National Biodiversity project and to make map for their distribution. Sixty three samples were collected ( 23 ♂ و 40 ♀) from Ras Alshamra and Ras Ibn Hani located at North of Latakia city during May, June ,July, andAugust 2018. Results showed that there are two new species first record at the littoral zone of Latakia, namely: Lysianassa costae (Lysianassidae) and Microdeutopus gryllotapla (Aoridae).